An Exploratory Study on the factors that cause stress and their impact on academic success: A cross-sectional qualitative study on postgraduate students using semi-structured interviews - Mahlagaume, Sanikie (The IIE, 2020)
The following study seeks to explore the factors that cause postgraduate students stress and hoe these affect their academic success. In so doing, the study seeks to discover the discrepancies that may exist between the way postgraduate students handle stress when compared to undergraduate students. This is due to the fact that literature found focused on the undergraduate student whereas those on postgraduate studies focused on the practical aspect (nursing) (Jithoo, 2017; Shete & Garkal, 2015). The study is qualitative in nature implying the use of qualitative methods. Thus, five postgraduate students were selected to partake in the study using non-probability, purposive sampling. Semi-structured interviews were used to give participants time to give a detailed overview of what stress means to them and its impact on their lives. Data acquired from the interviews was analysed using Zhang and Wildemuth’s eight step process of qualitative content analysis over a cross-sectional period of time (Maree, 2019). It was found that regardless of past experiences, new experiences made it just as difficult to handle stress. The results suggested that anxiety was a leading cause of stress which resulted in procrastination in terms of focusing on academics, experiencing helplessness (emotionally) and it affected decision-making.
Keywords: Stress causes; Academic success; Postgraduate students; Impact of stress